Dialect, language, nation: 50 years on - Joseph, John E.; Rutten, Gijsbert; Vosters, Rik (Language policy, 2020)
Over 50 years ago, the Norwegian-American linguist Einar Haugen published a seminal paper entitled ‘Dialect, language and nation’ (Am Anthropol 68:922–935, 1966b), in which he expounds his four-step model of standardization, explaining the development from dialect to standard following a process of norm selection, codification, acceptance and elaboration. In this article, we start by discussing the life and work of Einar Haugen, situating him within the history of linguistic thought throughout his career. Next, we zoom in on his standardization framework more specifically, discussing the relevant aspects of his four-box matrix, but also comparing his initial proposals to later influential publications on the subject expanding on his ideas, most notably by Milroy and Milroy (Authority in language. Investigating language prescription and standardisation, Routledge and Kegan Paul, London, 1985) and Joseph (The rise of language standards and standard languages, Frances Pinter, London, 1987b). Finally, we will proceed to give an overview of what we perceive to be major lacunae or shortcomings in Haugen’s standardization framework, focusing on specific elements missing, unclear or in need of refinement in one of the four originally defined steps, but also discussing Haugen’s fairly restrictive understanding of the directionality of language change, the narrow empirical scope of traditional standardization research, the crucial role played by ideology in the development of a standard variety, and the strong monolingual bias and relative absence of language contact in traditional accounts of standardization.